2011
DOI: 10.4149/neo_2011_03_217
|View full text |Cite
|
Sign up to set email alerts
|

Identification of site-specific prognostic biomarkers in patients with oral squamous cell carcinoma

Abstract: The purpose of the present study was to identify site-specific prognostic biomarkers in patients with oral squamous cell carcinoma (OSCC). For this purpose, Epidermal growth factor receptor (EGFR), Stat3, H-ras, c-myc, p53, cyclin D1, p16, Rb and Bcl-2 were localized immunohistochemically in buccal mucosa carcinoma (n=74) and tongue carcinoma (n=61) patients. Expression of markers was compared between buccal mucosa and tongue carcinoma and assessed for their prognostic value in site-specific manner. On compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 32 publications
2
33
1
1
Order By: Relevance
“…It also suggests that sialylation patterns vary site by site in all intra‐oral sites as the tongue carcinoma behaves entirely different. One of the studies has demonstrated that tongue carcinoma grows faster than other sites of the oral cavity and more frequently metastasize to cervical lymph nodes with a poorer prognosis . This suggests that elevated transcripts of STs and sialidase have a significant role in the aggressiveness of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…It also suggests that sialylation patterns vary site by site in all intra‐oral sites as the tongue carcinoma behaves entirely different. One of the studies has demonstrated that tongue carcinoma grows faster than other sites of the oral cavity and more frequently metastasize to cervical lymph nodes with a poorer prognosis . This suggests that elevated transcripts of STs and sialidase have a significant role in the aggressiveness of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…This proposition is supported by the varied frequency among different tumors or OSCC localizations of the activation of oncogenic mechanisms that upregulate cyclin D1. Thus, various authors (Mahdey et al , ; Trivedi et al , ; Huang et al , ) have reported that upstream cyclin D1 upregulating mechanisms (amplification, …) are more frequently activated in OSCC of the tongue versus other sites, although buccal mucosa carcinomas with CCND1 gene disorders are as aggressive as tongue carcinomas (Mahdey et al , ).…”
Section: Reflections and Future Research Linesmentioning
confidence: 99%
“…All the sections were scored independently, by two individual observers, in a blinded fashion. The scoring system has already been published in our previous literature (Trivedi et al, 2011). The sections were scored by assessing the site of staining which was cytoplasmic and using a semiquantitative score ranging from negative to 3+ (negative staining: 0-10% of cells positive, 1+: 11-30% of cells positive, 2+: 31-50% of cells positive , 3+: >50% of cells positive) was used.…”
Section: Immunohistochemistry and Evaluation Of Resultsmentioning
confidence: 99%
“…SOCS proteins are such type of molecules they have dual role in cancer depending on cancer cell origin. Oral squamous cell carcinoma (OSCC), a devastating neoplasm comprises a heterogeneous group of tumors which has different biological behavior and prognosis (Trivedi et al, 2011). Despite advances in treatment, they still represent a clinical challenge.…”
Section: Introductionmentioning
confidence: 99%